Penyuluhan Pemilahan Sampah Organik dan Anorganik di Tempat Pembuangan Sampah Dusun Bulu Desa Jaten Karanganyar - Susantiningrum Susantiningrum; Erika Dhantylistyanti Ariyanti; M. Mumtazul Fikri Nurfiansyah; Nadya Elvira (IAI Bunga Bangsa Cirebon, 2021)
This community service activity aims to improve the knowledge and skills of the community around the Bulu Village garbage dump, Jaten Village in sorting organic and inorganic waste. Service activities are carried out through focus group discussions, counseling, procurement of trash cans, evaluation of activities, as well as online and offline reporting. The participation and enthusiasm of the representatives of each Neighbourhood and Hamlet in the activity was very good, the partner groups, namely village-owned enterprises and Jaten Urban Village actively contributed in providing training needs and actively shared experiences in processing waste. The impact of community outreach activities is that they realize the importance of sorting waste from the smallest organizational structure and are able to apply it in their daily lives so that it is hoped that waste processing at Bulu Village garbage dump, Jaten Village can be controlled properly. Extension activities for sorting organic and inorganic waste in Bulu Village, Jaten Village is very useful and is expected to be sustainable. Abstrak Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan masyarakat sekitar tempat pembuangan sampah Dusun Bulu, Desa Jaten dalam melakukan pemilahan sampah organik dan anorganik. Kegiatan pengabdian dilaksanakan melalui metode focus group discussion, penyuluhan, pengadaan tong sampah, evaluasi kegiatan, serta pelaporan yang dilaksanakan secara daring maupun luring. Partisipasi dan antusiasme perwakilan masing-masing RT dan RW dalam kegiatan sangat baik, kelompok mitra yaitu pihak BUMDES dan Kelurahan Desa Jaten berkontribusi aktif dalam pengadaan keperluan pelatihan serta aktif berbagi pengalaman dalam mengolah sampah. Dampak dari kegiatan penyuluhan masyarakat menyadari akan pentingnya pemilahan sampah dari susunan organisasi terkecil serta mampu menerapkan dalam kehidupan sehari-harinya sehingga diharapkan pengolahan sampah di TPS Dusun Bulu Desa Jaten dapat dikendalikan dengan baik. Kegiatan penyuluhan pemilahan sampah organik dan anorganik di Dusun Bulu, Desa Jaten sangat bermanfaat dan diharapkan dapat berkelanjutan.